(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
بهدف تحديد الكميات المناسبة من الأسمدة الكيماوية( N,P,K) للحصول على أفضل إنتاج للأشجار و نوعية فقد تم استخدام عدة معاملات سمادية استخدام عدة معاملات سمادية لأشجار السفرجل من الصنف الصيداوي بعمر (14) سنة والمطعمة على الأصل البري للسفرجل وقد بينت النتائج: -1 للتسميد الكيماوي تأثير إيجابي في زيادة الإنتاج لأشجار السفرجل. -2 ساهم التسميد الكيماوي في زيادة محتوى الثمار من المواد الصلبة الذائبة والسكريات والحموضة وبالمقابل قلل من محتوى الثمار من فيتامين((C وخفّض من صلابة الثمار. -3 نقترح إضافة الكميات التالية من العناصر الغذائية لأشجار السفرجل بعمر (14) سنة والمزروعة في تربة لومية رملية : (300)غ ازوت نقي للشجرة ،(300)غ فوسفور نقي للشجرة ،(600)غ بوتاس نقي للشجرة To determine the appropriate amounts of chemical fertilizers to get the best production of trees as well as the best quality, several treatments of fertilizers were used. The study was conducted on Quince trees (Sidawi variety) aged 14 grafted on a wild quince stock. The results showed that: 1- the chemical fertilizer has a positive effect in increasing the production of quince trees. 2- The Chemical fertilizer caused an increase in the fruit content of total soluble solids, sugars and acidity. On the contrary both the vitamin (C) and firmness were reduced. 3- We propose to add the following quantities of nutrients to the quince trees (14) years old and planted in sandy Lomé soil: (300) g pure nitrogen for the tree, (300) g of pure phosphorus tree, (600) g of pure potash tree.